Comparative Advantage and Cost of Achieving Self-sufficiency for Vegetables and Fruits in the Sultanate of Oman - Baitsaid, Nasser Ali Musallam (2006)
The Sultanate of Oman has not achieved self sufficiency in the production of vegetables and fruits. This situation is due to the rapid growth in population that leads to a tremendous increase in the demand for these commodities and this deficit can only be sustained by imports. However, an increase in imports requires the use of more foreign exchange, which could otherwise be used for the importation of other important commodities. The expansion of domestic production would entail increasing the use of domestic resources thus raising the competition for the use of these resources. Therefore, the objective of this study is to determine the level of comparative advantage that Oman has for the different types of fruits and vegetables and the cost of producing these crops that will lead towards self-sufficiency in the country. Secondary data on the production of vegetable (tomatoes, cucumber, pepper, watermelon, melon and cabbage) and fruit crops (dates, lemon and banana) were collected from various government sources for the years 2000 to 2004. In order to estimate the cost of self-sufficiency this study analysed data on government intervention through the Nominal Protection Rate (NPR) and the Effective Protection Rate (EPR). The level of comparative advantage was analysed by using the domestic resource cost (DRC), resource cost ratio (RCR), net economic benefit (NEB) and social cost benefit (SCB) ratios. Based on the analysis of this research, the study found out that the country is self-sufficient only in pepper and dates while for the other selected crops the level of self-sufficiency was varied. The cost of achieving self-sufficiency for selected crop was estimated between R.O. 118,517 and R.O. 3,648,636 for the period under consideration. Additionally, government intervention on vegetable and fruit production showed that the average NPR of vegetables production under the import substitution regime ranged between 11% and 39% for vegetables and between 15% and 17% for fruits; whereas the average EPR ranged between 92% and 132% for vegetables and between 47% and 105% for fruits. Moreover, the RCR value of vegetable and fruit production generally showed that the country had a comparative advantage in the production of most of the crops to enable import substitution with the exception of lemon which recorded an RCR value of more than 1. This finding emphasised that through import substitution and an increase in domestic production, the Sultanate of Oman could save or earn foreign exchange.